Translanguaging among YouTubers: A Study of Language Use and Identity Construction - Sulistiawati, Bq. Lala; Yusra, Kamaluddin; Isnaini, Mh.; Arifuddin (Program Studi Pendidikan Bahasa Inggris, 2025)
This study explores the application of translanguaging by the YouTubers, focusing on language use, types of translanguaging, and how translanguaging is used to construct identity. The study used a netnographic method. The data were collected from the YouTube channels of Maudy Ayunda and Raymond Chin. The researcher first transcribed the utterances into written texts. Analysis of the transcripts was then done to determine what languages were used in the videos that demonstrated instances of multilingual application. In the research, it is observed that two languages are used, which are Bahasa Indonesia and English. Among these, Bahasa Indonesia is the dominant language. Once the languages have been identified the utterances were categorized into the types of translanguaging. The study reveals there are three types of translanguaging that include approximately 70 percent language mixing, 20 percent language choice and 10 percent language borrowing. Lastly, the researcher explained how these translanguaging practices contributed to identity construction. Each type of translanguaging constructs a specific identity: language mixing constructs a bilingual/ multilingual identity, language choice constructs a knowledgeable and educated identity, and language borrowing constructs a modern identity. While this study provides insights into digital translanguaging, its scope is limited to two YouTubers and therefore cannot fully represent the diversity of practices across the platform. Nevertheless, the study concludes that translanguaging functions not only as a means of communication but also as a performative tool for shaping and projecting identity in digital spaces.